2013
DOI: 10.1590/s0100-29452013000200027
|View full text |Cite
|
Sign up to set email alerts
|

Características físico-químicas, polifenóis e flavonoides amarelos em frutos de espécies de pitaias comerciais e nativas do Cerrado

Abstract: 3RESUMO -Apesar do grande potencial comercial da pitaia, ainda são escassos os estudos de caracterização físico-química de frutos da pitaia, principalmente considerando espécies nativas do Cerrado. Neste trabalho, objetivou-se analisar a caracterização físico-química, polifenóis e flavonoides amarelos totais de frutos de espécies de pitaia Hylocereus costaricensis, Hylocereus undatus, Selenicereus setaceus e Selenicereus megalanthus. Para as avaliações físico-químicas, foram realizadas as análises de sólidos s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1
24

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 14 publications
1
14
1
24
Order By: Relevance
“…Moreover, the polyphenols content was higher than that found by Piazzon et al (2010), who quantified phenolics in several types of beers, among which, wheat beer presented 504 ± 44 GAE mg/L. This increase can be explained by the fact that the cashew peduncle has considerable amounts of phenolic compounds (Lima et al, 2013).…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Moreover, the polyphenols content was higher than that found by Piazzon et al (2010), who quantified phenolics in several types of beers, among which, wheat beer presented 504 ± 44 GAE mg/L. This increase can be explained by the fact that the cashew peduncle has considerable amounts of phenolic compounds (Lima et al, 2013).…”
Section: Resultsmentioning
confidence: 60%
“…These results suggest that there should be a threshold in the concentration of polyphenols content to promote a significant effect on antioxidant activity. The presence of phenolic compounds and antioxidant activity in orange peel (Kelebek et al, 2009;Hegazy & Obrahium, 2012;Park et al, 2014;Davies et al, 2017) and cashew peduncle (Lopes et al, 2012;Lima et al, 2013;Andrade et al, 2015) have been confirmed in others studies. Moreover, formulations presented antioxidant activity values (Table 5) higher than those found by Marques et al (2017) in craft beers.…”
Section: Resultsmentioning
confidence: 63%
“…The yellow flavonoid content of the facheiro fruit's pericarp differed among the maturity stages (Table 4), showing that those phenolic compounds accumulated as maturation progressed: the content in G, IP, and R fruit was 0.74; 0.72, and 1.3 mg.100 g -1 , respectively. Lima et al (2013) reported a yellow flavonoid content of 6.03 mg.100 g -1 in pitayas (H. costaricensis), which, according to the authors, was 6-fold higher than in S. megalanthus fruit (0.88 mg.100 g -1 ). Thus, the yellow flavonoid content found in the facheiro pericarp in the present study is similar to that of S. megalanthus, but much lower than the other pitaya species, as evaluated by Lima et al (2013).…”
Section: Characteristicmentioning
confidence: 94%
“…Lima et al (2013) reported a yellow flavonoid content of 6.03 mg.100 g -1 in pitayas (H. costaricensis), which, according to the authors, was 6-fold higher than in S. megalanthus fruit (0.88 mg.100 g -1 ). Thus, the yellow flavonoid content found in the facheiro pericarp in the present study is similar to that of S. megalanthus, but much lower than the other pitaya species, as evaluated by Lima et al (2013). However, Dantas et al (2016) found that yellow flavonoids in T. inamoena increased from 1.51 to 5.21 mg.100 g -1 in the pulp and 1.14 to 9.11 mg.100 g -1 in the epicarp, during maturation.…”
Section: Characteristicmentioning
confidence: 94%
See 1 more Smart Citation